Innovation in the Development of E-LKPD Oeriented on Project Based Learning (Pjbl) Integrated with Steam in the Subject of Biology - Siti Nurfadhilah Mujaahidah Ahmad; Nurhayati B Nurhayati B; Rachmawaty Rachmawaty (Postgraduate, University of Mataram, 2025)
This study aims to produce a teaching material product in the form of e-LKPD oriented Project Based Learning integrated with STEAM in Biology Subject for Phase E SMA/MA Students which is valid, practical and effective. The subjects of the study were biology teachers and students of class X 5 SMAN 18 Makassar. This type of research is research and development (R&D) which adapts the ADDIE development model which has five stages, namely analysis, design, development, implementation, and evaluation. Validity data were collected through a product validation questionnaire on environmental change material. Practicality data were collected through student and teacher response questionnaires, and effectiveness data were collected through cognitive learning outcome tests. The data obtained were analyzed using descriptive statistical analysis. The results showed that the average value of the total validity and product development was in the very high validity category (1). The response results meet the criteria of practicality because the average student response to product development is in the very practical category (85.22%) and the average teacher response value to product development is in the very practical category (93.31%). Product development meets the criteria of effectiveness because the average N-gain value of each student is in the moderate category (0.7).